PENGARUH EKSTRAK KULIT BATANG ANGSANA (Pterocarpus indicus Willd.) TERHADAP KONSUMSI PAKAN WALANG SANGIT (Leptocorisa oratorius Fabricius) - Suarna, Mailastri; Sumarmin, Ramadhan; Lusi, Armen (STKIP PGRI Sumbar, 2013)
ABSTRACTWalang rice pest is a pest that attack rice plants after flowering by sucking liquidgrain and causes the grain to be empty or incomplete filling. This pest can reduce not only the results but also degrade the quality of grain such as brown spots on the grain. Angsana bark extract expected to be antifeedant to walang rice pest .The aim of this to determine the effect of angsana bark extract on feed intake Angsana walang rice pest .This research used Completely Randomized Design ( CRD ) with 4 treatments and 8 replications . Angsana bark extract treatment given is 0 % , 2.5 % , 5 % and 7.5 % . Data were analyzed using ANOVA test and if followed by LSD test . The research was conducted in April-June in the Laboratory of Zoology Department of Biology Faculty padang state university.The results showed that in the control treatment searching activity walang rice pest of takes the fastest31 minutes 62 seconds compared to other treatments . For grounding activity found in the fastest the control 19 minutes 34 seconds while on treatment with a gathering activity concentration of 5 % takes a quickes 11 minutes 8 seconds . On feed consumption Angsana bark extract in the treatment and control concentrations of 5Â % indicates the average number of the lowest feed intake of 0.53 % . It can be concluded that the influence of Angsana bark extract at a concentration of 5 % can be used as an antifeedantto walang rice pest .Â Â